Propuesta de un manual de funciones, reglamento de admisión y empleo, y valuación de puestos por puntos en la clínica San Pablo de la ciudad de Loja - Espíndola Camacho, Juan Carlos (2017)
Materials and methods that were established to run the research were: the Situational diagnosis clinic San Pablo was necessary to make use of a methodological and systematic process starting from direct observation that served to first-hand soak up reality in everyday activities, their structure, as well as we could also gather information about staff and activities carried out by each worker is handled. The following methods were also used: deductive, inductive, analytical, scientific, and statistical. The objective of the present project entitled "PROPOSAL FOR a MANUAL FUNCTIONS, REGULATION OF ADMISSION and EMPLOYMENT, and VALUATION OF POST BY POINTS AT THE CLINIC SAINT PAUL IN THE CITY OF LOJA", it is to develop a Manual of classification of posts and valuation for points, for the clinical Sao Paulo, with the aim that the company subject of study, having a tool that allows you to improve the management of human talent with spaces and functions so that each worker fulfills the specific objectives of your position and this leads to the achievement of the goals of the clinic. The conceptual part consolidates the necessary theoretical basis for the elaboration of the proposal, the review of issues related to the problems that bring and consolidate a proper scientific basis. While the results it is noted the diagnosis the clinical Sao Paulo in order to determine the shortcomings that exist and subsequently, with the valuation of positions failed to verify if staff are receiving a fair salary based on the charge that plays. The discussion of results, is composed of the collected information which suggests the following: control and management of the resources of the clinic St. Paul makes it in an empirical way, not administrative manuals therefore staff not has clear main functions, activities and requirements required by to perform efficiently, and finally there is the valuation of positions, since they lack expertise.